2013
DOI: 10.1017/s0007114512005302
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a probiotic fermented milk on the thymus in Balb/c mice under non-severe protein–energy malnutrition

Abstract: Protein -energy malnutrition (PEM) causes a significant impairment of the immune system, the thymus being one of the most affected organs. It has been demonstrated that the administration of probiotic fermented milk (PFM) recovered the intestinal barrier, histological alterations and mucosal and systemic immune functions in a non-severe malnutrition model using BALB/c mice. The aim of the present study was to evaluate, in the same model of malnutrition, the effect of a PFM added to a re-nutrition diet on the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
17
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 20 publications
3
17
0
Order By: Relevance
“…Thymus histology was recovery after yogurt supplementation, being probiotic yogurt more effective, showing a similar structure to the normal control. This effect was observed previously with other probiotic milk [25]. Low fat milk supplementation did not have effect on thymus histology.…”
Section: Resultssupporting
confidence: 88%
“…Thymus histology was recovery after yogurt supplementation, being probiotic yogurt more effective, showing a similar structure to the normal control. This effect was observed previously with other probiotic milk [25]. Low fat milk supplementation did not have effect on thymus histology.…”
Section: Resultssupporting
confidence: 88%
“…The authors also observed a decrease in the cellular apoptosis of this organ and a recovery of the CD4 + and CD8 + single-positive thymocytes. Besides, an increase in different cytokines in the thymus of the mice fed with PFM was also reported [78].…”
Section: Mechanisms Induced By Probiotics To Stimulate the Immune Systemmentioning
confidence: 89%
“…These antibodies have been shown to play a critical role in decreasing the spread of pathogenic bacteria to the liver and the spleen after a challenge with S. typhimurium. This effect has shown to be more remarkable in an undernourishment model [78].…”
Section: Mechanisms Induced By Probiotics To Stimulate the Immune Systemmentioning
confidence: 91%
See 1 more Smart Citation
“…In this context, Cani et al (16) reported that changes in gut microbiota (following a high-fat diet or genetically induced obesity) contribute to increased gut permeability, metabolic endotoxemia [higher serum lipopolysaccharide (LPS) levels], and low-grade inflammation-induced metabolic disorders (insulin resistance and diabetes), while its restoration by prebiotic and probiotic strategies ameliorate those adverse effects. Potential probiotic strains have been shown to play a role in nutritional disorders, including both under and overnutrition in human and animal studies (17–25). …”
Section: Introductionmentioning
confidence: 99%